Integrated Multi-Trophic Aquaculture: A Laboratory and Hands-on Experimental Activity to Promote Environmental Sustainability Awareness and Value of Aquaculture Products - Correia, Marta; Azevedo, Isabel Costa; Peres, Helena; Magalhães, Rui; Oliva-Teles, Aires; Almeida, Cristina Marisa Ribeiro; Guimarães, Laura (Frontiers in Marine Science, 2020)
Aquaculture is among the industries growing at a fastest rate in the world. This industry has been recognised to play a critical role in food production for a continuously expanding world population. However, despite various technological innovations and improvements in production techniques, this sector is still associated with misperceptions and negative opinions hampering its implementation and wide consumption of its products. The integrated multi-trophic aquaculture (IMTA) concept was developed as a way to increase sustainability of intensive aquaculture systems, using an ecosystem-based approach. In this study, following this sustainable aquaculture concept, a closed recirculation IMTA system, at laboratorial scale, was developed and tested with the simultaneous production of fish, sea urchin and seaweed for 70 days. Based on this proof of concept, a hands-on experimental activity was developed to teach and communicate recent scientific advances in environmental sustainability and value of aquaculture products to young students and the general public. This experimental activity was tested and evaluated with students (n = 60) of basic and high-school (secondary) learning cycles. A quantitative assessment was carried out through a short questionnaire provided to the students before and after the experimental activity. After the experimental activity, a qualitative assessment was also performed through questions expressed without preconceived categories or hypotheses. Results indicated that the overall frequency of students who consider the ocean to be “very important” and “extremely important” increased from 68% to 81% after performing the experimental activity. Moreover, the percentages of correct answers to the questions related to IMTA concepts also increased significantly after the experimental activity. In the discussion of the experimental activity results, the students stated that they appreciated the opportunity to develop a hands-on experimental activity, which allowed them to increase their knowledge and obtain information on aquaculture and the quality of its products.